Studi Ekman Mass Transport dan Ekman Pumping Velocity pada Kawasan Perairan Selatan Jawa – Nusa Tenggara - Nindy Saitama L. Gaol; I Wayan Gede Astawa Karang; I Dewa Nyoman Nurweda Putra (Indonesian Physical Review, 2026)
The waters south of Java to Nusa Tenggara are a critical upwelling region heavily influenced by monsoon dynamics. The interactions drive oceanographic variability, specifically Ekman Mass Transport (EMT) and Ekman Pumping Velocity (EPV), which regulate primary productivity. While previous studies have examined these dynamics, most have focused on short-term variations. To address this, this study analyzes the variability of EMT and EPV over a 22-year period (2003–2024) and their interaction with El Niño-Southern Oscillation (ENSO) and Indian Ocean Dipole (IOD). EMT and EPV values were calculated using ECMWF wind data, SST, and chlorophyll-a data sourced from MODIS, and climate indices (Niño 3.4 and DMI), which were then analyzed using Pearson correlation. Results show that EMT and EPV peak during the Southeast Monsoon (JJA), reaching approximately 5.16 m²/s and -2.89 × 10⁻⁵ m/s, respectively. Notable anomalies occurred in 2010 and 2016; specifically, the 2010 interaction between La Niña and a negative IOD significantly suppressed upwelling. Correlation analysis reveals that SST is predominantly influenced by EPV, while chlorophyll a concentration is more closely linked to EMT. Although both ENSO and IOD modulate these dynamics, the IOD exerts a stronger influence due to the region’s proximity to the Indian Ocean. These findings provide critical insights into the oceanographic drivers of regional productivity, supporting sustainable fisheries management.